(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Work Life Balance is an important element of QWL which include the variables Reading books, Listening to music, Priorities and plan work, Shares with family take into confidence, Inviting friends or relatives, Having holiday, gym, yoga, walk, playing an instrument, Defining work and life boundaries, Good working relationship, Accepting the fact that respondents cannot be everything to everyone etc